Altered Functional Interactions of Inhibition Regions in Cognitively Normal Parkinson’s Disease - Harrington, Deborah L.; Shen, Qian; Theilmann, Rebecca J.; Castillo, Gabriel N.; Litvan, Irene; Filoteo, J. Vincent; Huang, Mingxiong; Lee, Roland R. (Frontiers in Aging Neuroscience, 2018)
Deficient inhibitory control in Parkinson’s disease (PD) is often observed in situations requiring inhibition of impulsive or prepotent behaviors. Although activation of the right-hemisphere frontal-basal ganglia response inhibition network is partly altered in PD, disturbances in interactions of these regions are poorly understood, especially in patients without cognitive impairment. The present study investigated context-dependent connectivity of response inhibition regions in PD patients with normal cognition and control participants who underwent fMRI while performing a stop signal task. PD participants were tested off antiparkinsonian medication. To determine if functional disturbances depended on underlying brain structure, aberrant connectivity was correlated with brain volume and white-matter tissue diffusivity. We found no group differences in response inhibition proficiency. Yet the PD group showed functional reorganization in the long-range connectivity of inhibition regions, despite preserved within network connectivity. Successful inhibition in PD differed from the controls by strengthened connectivity of cortical regions, namely the right dorsolateral prefrontal cortex, pre-supplementary motor area and right caudal inferior frontal gyrus, largely with ventral and dorsal attention regions, but also the substantia nigra and default mode network regions. Successful inhibition in controls was distinguished by strengthened connectivity of the right rostral inferior frontal gyrus and subcortical inhibition nodes (right caudate, substantia nigra, and subthalamic nucleus). In both groups, the strength of context-dependent connectivity correlated with various indices of response inhibition performance. Mechanisms that may underlie aberrantly stronger context-specific connectivity include reduced coherence within reorganized systems, compensatory mechanisms, and/or the reorganization of intrinsic networks. In PD, but not controls, abnormally strengthened connectivity was linked to individual differences in underlying brain volumes and tissue diffusivity, despite no group differences in structural variables. The pattern of structural-functional associations suggested that subtle decreases in tissue diffusivity of underlying tracts and posterior cortical volumes may undermine the enhancement of normal cortical-striatal connectivity or cause strengthening in cortical-cortical connectivity. These novel findings demonstrate that functionally reorganized interactions of inhibition regions predates the development of inhibition deficits and clinically significant cognitive impairment in PD. We speculate that altered interactions of inhibition regions with attention-related networks and the dopaminergic system may presage future decline in inhibitory control.